Systematic Literature Review: Interactive Learning Media Based on the ARSELTHK Model to Enhance Students’ Mathematical Concept Understanding and Character Development - Ermawati, Ni Made Dewi; Ardana, I Made; Suweken, Gede (Darul Yasin Al Sys, 2025)
Although interactive learning media and character-based educational approaches have received increasing attention in prior studies, research explicitly integrating collaborative models, Social Emotional Learning (SEL), and Tri Hita Karana (THK) values within a unified framework such as ARSELTHK remains limited. This study aims to systematically examine the characteristics, effectiveness, and research gaps in interactive learning media designed to enhance mathematical concept understanding and student character development. A qualitative approach was employed using a Systematic Literature Review (SLR) design guided by the PRISMA protocol, involving 22 selected journal articles obtained through purposive sampling from Scopus and Google Scholar databases. Data were collected through document analysis and synthesized using descriptive and thematic analysis. The findings indicate that interactive learning media consistently improve students’ conceptual understanding, particularly in topics such as simple and compound interest, while studies integrating THK and SEL demonstrate significant contributions to character formation, emotional regulation, and contextual learning. Collaborative models involving teachers, parents, and students also emerge as essential for strengthening student character. These results contribute to the theoretical development of culturally grounded, holistic learning frameworks and expand understanding of integrated character-based mathematics instruction. The study concludes that ARSELTHK-oriented interactive media play a crucial role in promoting both cognitive and character outcomes in mathematics education and recommends that educators and curriculum developers adopt integrated cultural–emotional–collaborative approaches when designing digital learning media. The implications include theoretical contributions to the literature on holistic mathematics learning and practical recommendations for schools to strengthen culturally responsive and character-oriented pedagogy, while highlighting opportunities for future research on long-term effectiveness, large-scale implementation, and empirical validation of ARSELTHK-based media.